The Significance of the Family in Russian Paremics: Linguistic and Cultural Aspect - L.R. Akhmedshina (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article pays special attention to linguoculturology. The ideas about the role of husband and wife in Russian proverbs are considered.